Comparison of Educational Media with Video and Pop-Up Book Towards Knowledge of Balanced Nutrition Guidelines in Elementary School Students - Putri, Endah Budi Permana; Noviani, Eka Okta (Jurnal Pendidikan Anak, 2021)
The unbalanced eating behavior of school-age children is influenced by the level of nutritional knowledge. The purpose of this research is to analyze the comparison of media education with videos and pop-up books on the knowledge of balanced nutrition guidelines for elementary school students. This type of research is a quasi-experimental design with a nonequivalent control group design. The total sample used in the study was 90 students who were taken by probability sampling and then divided into two groups, 45 students were given education with video media (P1) and 45 students were educated with pop-up book media (P2). Data were analyzed using the Wilcoxon and Mann-Whitney test with a significant level of 0.05. The results obtained are that there is a difference in the level of knowledge of the pop-up book group before and after education (p=0.0001) and there is no difference in the level of knowledge of the video group before and after education (p=1.00). Pop-up book media is more effective in increasing students' knowledge level of balanced nutrition compared to video, so pop-up book media can be an alternative media used to provide education to elementary school students.